Heterocyclic Substituted Flavones: Bridging Natural Products and Medicinal Chemistry - Sohit Lal; Satish Kumar Sarankar (International Journal of Tropical Medicines, 2024)
Heterocyclic substituted flavones represent a unique and promising class of flavonoid derivatives, gaining significant attention in recent years due to their diverse and enhanced biological activities. These compounds are characterized by the incorporation of heterocyclic moieties such as quinoline, pyridine, thiazole, imidazole, oxazole, and pyrazole into the flavone structure, which significantly alters and often enhances their bioactive properties. This structural modification has made heterocyclic flavones particularly appealing as candidates for therapeutic applications. The inclusion of heterocyclic groups in flavones not only diversifies their chemical structure but also imparts a wide range of biological activities. Among these, their antioxidant, anti-inflammatory, antimicrobial, and neuroprotective properties stand out, with particular emphasis on their potential as anticancer agents. Moreover, the mechanisms underlying the biological activities of heterocyclic flavones are explored, offering insights into how these compounds interact at the molecular level to exert their effects. This understanding is crucial for the rational design of new derivatives with improved efficacy and selectivity. The growing interest in heterocyclic flavones is fueled by their potential to address various unmet medical needs, particularly in the development of new drugs and therapeutic agents. This review highlights the importance of continued research in this field, particularly focusing on innovative modifications that could unveil new biological activities. By expanding our knowledge of flavonoid chemistry and the therapeutic applications of heterocyclic flavones, there is a significant opportunity to develop novel treatments that could benefit patients across a range of conditions.
Keywords: Anticancer Potential; Flavone derivatives; Heterocyclic Substituted Flavones; Structure-Activity Relationships; Therapeutic Applications